PENGARUH JOB EMBEDDEDNESS TERHADAP KUALITAS KEHIDUPAN KERJA DAN PERILAKU KEWARGAAN ORGANISASIONAL (Studi pada Kantor Administrasi Biro Universitas Syiah Kuala) - Khairul Anam, Fairuzzabadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2016)
This research was conducted to find the effect of job embeddedness to the quality of work life and to the organizational citizenship behavior of the staff of University of Syiah Kuala Biro Administration. The sample used in this research are the staff of University of Syiah Kuala Biro Administration whom totaled 329 respondents. The instrument of collecting data in this research is questionnaire. Random sampling was used as sampling technique. As much of 150 questionnaires distributed and only just 110 questionnaires could be collected. Linear regression analysis was used as a method of analysis to determine the effect of all variables involved in this research. The results showed that: 1) job embeddedness significantly effect to quality of work life of the staff of University of Syiah Kuala Biro Administration. 2) job embeddedness significantly effect to organizational citizenship behavior of the staff of University of Syiah Kuala Biro Administration.  Keyword: Job Embeddedness, Quality of Work Life, Organizational Citizenship Behavior.